An Approach to Polar Research - Jones, T.O. (ARCTIC, 1963)
Discusses role of the National Science Foundation in U.S. research in the Arctic and Antarctic. For the latter NSF has fostered a coordinated basic research program. Some features of it and techniques developed might be utilized in a bipolar program on problems of common interest, e.g. conjugate phenomena of the upper atmosphere, international cooperation, etc. Proposals for basic research in the Arctic are welcomed.